Impact of deposit recoat cycle length on hot corrosion of CMSX-4 - Sumner, Joy; Aksoul, Quentin; Delgado, Joemar; Potter, Andrew; Gray, Simon (Springer, 2017)
Hot corrosion causes significant problems for both aerospace and power generation industries, where the combination of high temperature, corrosive gases, and contaminants severely limits component operating lifetimes in gas turbine hot gas streams. Multiple laboratory testing methodologies exist to study this hot corrosion, and these can be affected by a range of variables. This paper investigated the impact of varying deposit recoat cycle length when using the ‘deposit recoat’ testing method. CMSX-4 samples were exposed to simulated type II (pitting) hot corrosion conditions, with the same overall deposit load (averaged across the total exposure run), but different deposit recoat cycles. Post-exposure, samples underwent dimensional metrology analysis to compare metal loss resulting from different deposit recoat cycle lengths. Results for CMSX-4 suggest very small differences in corrosion losses, indicating CMSX-4 hot corrosion datasets obtained from deposit recoat experiments with different deposit recoat cycle lengths can be compared with confidence.
Keywords: Deposit recoat period; Type II hot corrosion; CMSX-4; Dimensional metrology